Implementation of continuity editing in making CDA IPB University Profile Videos - Saepudiqri, Saepudiqri; Pranata, Rici Tri Harpin (The International Journal of Politics and Sociology Research, 2024)
Audio-visual media as an effective communication tool is increasing in today's digital era. CDA IPB is one of the work units that carries out programs on the importance of preparing students to succeed in the world of work. The purpose of this final project is to explain the creation flow of CDA IPB profile videos and implement continuity editing in the flow of making CDA IPB profile videos. In addition, in making the video, the editor applies an editing technique, namely continuity editing and Multimedia Development Life Cycle (MDLC), so that the visuals in the video contain continuity and are related to each other. The result of this final project is that an institution needs a short profile video-based information container that can be accessed by parties related to CDA. This profile video has been compiled based on editing techniques, namely continuity editing so that the resulting video can be watched comfortably and the information is conveyed clearly. The result of this final project is a video profile of Career Development and Assessment (CDA) which has gone through the stages of planning, discussion, execution, and completion. When completing the profile video, an editor uses the Multimedia Development Life Cycle (MDLC) method approach, namely assembly (assembly) and testing (testing). Following the stages of the MDLC method, namely testing carried out on profile videos, an interpretation was obtained which showed very satisfactory results with a percentage of 90.08 percent. The main essence of this final project is making the latest profile video from CDA, by implementing the latest things in the profile video. After the profile video has been created, testing is carried out to measure how perfect the latest profile video is compared to the previous one.